A Book Review on Making Capitalism Work for the Poor and Society (Written by Yunus, Muhammad, and Karl Weber. 2007) - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2012)
Professor Yunus and Karl Weber argue that neither the profit-maximizing business nor the other conventional approaches adopted by nonprofit organizations and multilateral funding agencies can provide a sufficient answer to the problem of persistent poverty and many social problems that we see in the world. The corporate social responsibility approach of profit-maximizing businesses will not work either. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 115-119 Uploaded date: July 8, 2012